The Internationalisation of Banks: A Multilevel Analysis of Positive Effects in Regard to Competitiveness - Oksana Kiforenko (Problemy Zarządzania, 2016)
The objective of this paper is to analyze the nature and characteristics of the relationship between internationalisation and competitiveness and to analyze the impact and potential limits of this relationship on the development of the banking system as a whole and on single banks in particular. The study is based on secondary data derived from EU legislative acts, official state statistics of Ukraine, Germany, and the European Union. The paper employs the following methods: critical analysis method, statistical analysis, the method of ratings, and the case study method. Multilevel analysis was conducted on the EU, country level (Ukraine and Germany), and company-level (Deutsche Bank). Internationalisation is an important factor that leads to the increase of the competitiveness level. The study results suggest that internationalisation increased competition, which in turn influenced the activity of the banking system as a whole in both Ukraine and Germany positively. The study suggests that internationalisation processes contribute immensely to the raising of the competitiveness level of banks. Yet, it also identified the problem of the limits of internationalisation up to which the said activity brings the company profits, but after crossing of which, the company is overloaded with too many branches abroad or foreign market segments, where it functions. The originality of this work lies in studying the nature and relationship of competitiveness and internationalisation of banks and in comparing the impact of the mentioned concepts on the development of the banking system on three levels of analysis.